Government policy: meaning, types, manifestations, theories, and policy cycles - Adetayo Olaniyi Adeniran; Joseph Mosunmola Muraina; Joseph Olanrewaju Ilugbami; Adedayo Ayomide Adeniran (Insights into Regional Development)
In any democracy, it is strongly advised that effective policies be created since they are crucial to how democracies operate. Government policy definitions and categories were widened. Government policy types were discussed concerning the sectoral groups comprising each given government. This is important because a policy’s or its objective elements frequently suggest different meanings for different stakeholders. Policymaking is a process impacted by socio-political and other factors and is not a governmental function. Thus, there is a need to comprehend the theoretical underpinnings on which government policymaking and its execution may be evaluated and characterized. According to the elite/mass hypothesis, there are two groups in society: those who occupy positions of power and those who do not. Government policy is more influenced by those with access to knowledge and influence. It is a remarkable characteristic of group theory which is ideally in line with the legislative because the legislatures are where the voices of the people are expressed. Governmental institutions and government policy are closely related, claims institutional theory. The rational choice theory may need to be more accurate since participants in government policy must have access to all information to make informed judgments. The systems theory offers a more straightforward method for categorizing and comprehending the contributions and interrelationships made by institutions and policy players, including the function played by the external environment in policy formulation. Lastly, since democracy is a system of governance built on extensive public engagement, any ideology that supports any type of citizen participation (particularly in a democracy) should be endorsed by both politicians and public officeholders.